Mental Wellbeing during the Lockdown Period following the COVID-19 Pandemic in Nepal: A Descriptive Cross-sectional Study - Carmina Shrestha; Calvin Ghimire; Sajan Acharya; Prabhat KC; Swarndeep Singh; Pawan Sharma (Journal of Nepal Medical Association, 2020)
Introduction: COVID-19 pandemic has profoundly affected all aspects of society, including mental and physical health. Often missed is the fact that the pandemic is occurring against the backdrop of a very high prevalence of mental health issues. Protecting the mental health of people and healthcare workers is important for long-term positive health outcomes and proper control of the outbreak.